Individual Education Program Kaitannya dengan Differentiated Assessment: Strategi Mengakomodir Siswa Berkebutuhan Khusus di Sekolah Umum - Dina Sekar Vusparatih (Bina Nusantara University, 2011)
Individual Education Program (IEP) is a plan made by a team consists of parents, teachers, and other school elements. The purpose of IEP is to help students reach expected academic target. IEP is designed for students in special needs that not only defined academic target but also the methods for reaching the target. Thearticle explains the stages in defining IEP. The primary purpose of IEP is to give the same chance for students with special needs to have standard and public school education for other normal students. Through public schools, the students with special needs could interact and socialize with other students.